Probiotics and Bioactive Carbohydrates in Colon Cancer Management - Raman, Maya.; Ambalam, Padma; Doble, Mukesh; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
This book describes the dietary habits (such as use of probiotics, synbiotics, prebiotics and dietary fiber) that could modify and reduce the risk of developing colorectal cancer (CRC). The book will be of practical and scientific use to academicians, research scholars, students, health professionals, nutritionists, etc. and could support the cause of preventing CRC by adopting smarter food habits. CRC is the third leading cause of death, in terms of both incidence and mortality, among men and women. Excess consumption of red and processed meat, roasted coffee, etc. have shown an increase in CRC, indicating that compounds formed in food containing free amino acids and sugars interact at elevated temperatures to form mutagens or carcinogens. Standard treatment options for CRC include invasive surgery and chemotherapy or radiation. Several lifestyle and dietary factors could prevent this ailment. Probiotics, prebiotics and synbiotics that are found in functional foods, health supplements and nutraceuticals and short chain fatty acids that are formed in the colon as a result of microbial fermentation of undigested bioactive carbohydrates by Bifidobacterium and Lactobacillus inhibit colonic epithelial cells and minimize inflammation, thereby exhibiting immunomodulatory effects. This book tries to address the novel unexplored benefits and mechanism of action of these functional foods.
1. Introduction -- 2. Probiotics and Colorectal Cancer -- 3. Bioactive Carbohydrate- Dietary Fibres and Colorectal Cancer -- 4. Bioactive Carbohydrate- Prebiotics and Colorectal Cancer -- 5. Synbiotics and Colorectal Cancer -- 6. Short Chain Fatty Acids -- 7. Conclusion.
Keywords: Food science; Cancer; Biochemistry; Food Science; Cancer Biology; Biochemistry